2006
DOI: 10.1097/01.ede.0000220553.84350.c5
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Biphenyls, Polychlorinated Biphenyls, Body Weight, and Incidence of Adult-Onset Diabetes Mellitus

Abstract: We found no association between PBB serum levels and diabetes incidence. In women, there was a positive linear association of diabetes incidence with PCB serum levels at enrollment. This finding is in agreement with 2 prior studies indicating a higher relative risk of diabetes in PCB-exposed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
109
6
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 36 publications
18
109
6
3
Order By: Relevance
“…Longnecker et al (3) revealed a 30% higher level of total PCBs in diabetic (primarily type 1) pregnant women than in nondiabetic subjects recruited in 1959 -1966. Similar conclusions were drawn from the National Health and Nutrition Examination Survey (NHANES) (4) and other population studies in Belgium (5), Michigan (6), and Seveso, Italy (7). These data raised great concerns for public health (8) and promoted etiological research into the biological effects of POPs (9,10).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Longnecker et al (3) revealed a 30% higher level of total PCBs in diabetic (primarily type 1) pregnant women than in nondiabetic subjects recruited in 1959 -1966. Similar conclusions were drawn from the National Health and Nutrition Examination Survey (NHANES) (4) and other population studies in Belgium (5), Michigan (6), and Seveso, Italy (7). These data raised great concerns for public health (8) and promoted etiological research into the biological effects of POPs (9,10).…”
supporting
confidence: 62%
“…In the Michigan follow-up study of the effects of exposing farmers and other households to animal feed contaminated with PCBs, women experienced twice the incidence of self-reported type 2 diabetes when total PCBs exceeded 5 ppb, but there was no increased diabetic risk for men (6). The 20-year follow-up study of the Seveso cohort, highly exposed to tetra-chlorinated dibenzo-p-dioxin after a factory incident in 1976 (7), showed that the mortality rate from diabetes had significantly doubled for women residing in the exposure area compared with women residing in the reference area but that the relationship was not present in men.…”
Section: ])mentioning
confidence: 99%
“…This nonlinear dose-response curve may explain previous epidemiological findings in the Michigan cohort with accidental high exposure to PBBs (20). In fact, this prospective cohort study did not show any association between PBB concentrations and incident diabetes.…”
mentioning
confidence: 41%
“…Several reports based on mortality rates analysis [6,7] or on self-reported diabetes also show associations between environmental pollution levels and prediabetes and/or diabetes [8][9][10]. However, in only few studies was diabetes diagnosed with the aid of fasting plasma glucose (FPG) (≥126 mg/dl [7.0 mmol/l]), HbA 1c (>6.1%) [9] or random glucose level (≥200 mg/dl=11.1 mmol/l) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%